Selective Vesical Artery Embolization in Refractory BK Virus Hemorrhagic Cystitis - Kumar, Saurabh; Bhargava, Rahul; Kumar, Meet; Dua, Vikas; Santosh, Santosh (Journal of Clinical Interventional Radiology ISVIR, 2023)
In hematopoietic stem cell transplantation (HSCT) recipients, BK virus-related hemorrhagic cystitis is a well-known complication. It increases the risk of death and morbidity of HSCT recipients with simultaneous increase in healthcare cost burden, as a result of prolonged hospital admissions. There are many conservative therapeutic strategies available for the treatment that are effective in treatment of milder forms of hemorrhagic cystitis. Vesical artery embolization is one of the nonsurgical bailout procedure in patient's refractory to medical therapy with added advantage of avoidance of high-risk definitive surgical procedure of cystectomy or urinary diversion in these critical immunosuppressed patients.
Keywords: hematopoietic stem cell transplantation; BK virus; hemorrhagic cystitis